Avaliação na Educação Infantil: o que nos revelam os relatórios de um município paulista - Bresciane, Ana Lúcia Antunes (2015)
Assessment has been a centered subject of debates in the area since EI was established as the first stage of basic education. Children are placed in educational institutions therefore it is essential to pay devoted attention to the studies on EI assessment towards the creation of a guideline that aims the structure of appropriated models and practices to the segment. The problem of this research consisted in the following question: How do teachers assess children's progress in early childhood education? The study s goal was to investigate what the monitoring reports reveal about the EI assessment conceptions and practices in a public school chain from a city of São Paulo State. For the data production, 56 biannual monitoring and evaluation reports of 20 students that attended preschool in 5 EMEIs between 2013 and 2014 were collected. Some results were brought by quantitative analysis, but qualitative analysis was also used to explain the data. The results show that: 1. there is a common curriculum organization to all schools, based on the National Curricular Framework for Early Childhood Education, from which the assessment is carried out; 2. all schools produce the same type of record, following what is proposed in the county regiment and following the same template; 3. the educational context and children's learning are not listed in the assessment; 4. evaluation preferably focuses on the contents of the axes of Mathematics, Oral and Written Language, Personal and Social Education; 5. the assessment focus are the results of the mentioned content, not the process of learning and development; 6. families participate little, just by the end of the evaluation process, and the children do not participate. These results indicate that the curriculum purpose, along with the evaluation procedures, need to be reviewed and changed in some aspects for them to meet in consonance with the DCNEI principles and guidelines and with what has been recommended by the most current literature. Points to the continuing education as a means to carry out such tasks and contribute to the realization of a good quality EI in the studied city, as well as those that require the same interventions